2007
DOI: 10.1161/circresaha.107.150201
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Progenitor Cells Isolated From Human Embryonic Stem Cells Give Rise to Endothelial and Smooth Muscle–Like Cells and Form Vascular Networks In Vivo

Abstract: Abstract-We report that human embryonic stem cells contain a population of vascular progenitor cells that have the ability to differentiate into endothelial-like and smooth muscle (SM)-like cells. Vascular progenitor cells were isolated from EBs grown in suspension for 10 days and were characterized by expression of the endothelial/hematopoietic marker CD34 (CD34 ϩ cells). When these cells are subsequently cultured in EGM-2 (endothelial growth medium) supplemented with vascular endothelial growth factor-165 (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
188
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(203 citation statements)
references
References 34 publications
10
188
1
2
Order By: Relevance
“…21,113 Additional studies of ESCs differentiated to form endothelial cells and smooth muscle cells have shown the ability of these cells to integrate into the host circulation. 57,114 Indeed, ESC-derived endothelial cells have been shown to enhance revascularization in models of hindlimb ischemia and MI. 115,116 In a recent study tracking the fate of ESC-derived endothelial cells, survival of transplanted cells into infarcted murine myocardium was detected at 8 weeks post-infarct with functional improvement and increased vascular density.…”
Section: Embryonic Stem Cells (Escs) and Reprogrammed Somatic Cellsmentioning
confidence: 99%
“…21,113 Additional studies of ESCs differentiated to form endothelial cells and smooth muscle cells have shown the ability of these cells to integrate into the host circulation. 57,114 Indeed, ESC-derived endothelial cells have been shown to enhance revascularization in models of hindlimb ischemia and MI. 115,116 In a recent study tracking the fate of ESC-derived endothelial cells, survival of transplanted cells into infarcted murine myocardium was detected at 8 weeks post-infarct with functional improvement and increased vascular density.…”
Section: Embryonic Stem Cells (Escs) and Reprogrammed Somatic Cellsmentioning
confidence: 99%
“…those isolated from native blood vessels) is inherently limited because acquiring them demands an invasive procedure, they are typically available in insufficient quantities and they exhibit a low rate of proliferation (Shin'oka et al, 2001;Koike et al, 2004;L'Heureux et al, 2006). Thus, in order to advance vascular tissue engineering, stem cells have been intensively explored as alternative sources for both mature endothelial cells and SMCs (Ferreira et al, 2007). Among the various stem cell types that are suitable for application in vascular grafts, mesenchymal stem cells (MSCs) have been most extensively studied to date (Seifu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The use of hESC-derived ECs in regenerative medicine has also been reported. 14,15 However, hESCs face the potential problem of sourcing and host immune rejection. 16 Alternatively, there is significant evidence demonstrating the angiogenic potential of endothelial progenitor cells (EPCs), including those of adult origin.…”
Section: Introductionmentioning
confidence: 99%